PAKAD holds workshop to help SPM students master Science subjects - Fatmawati, Adam (2019)
Lecturers from the Academic Association (PAKAD) of Universiti Malaysia Pahang (UMP) recently held an academic intensive workshop to help Form Five students at Sekolah Menengah Kebangsaan Agama Pahang (SMKAP) in Muadzam Shah prepare for their Sijil Peperiksaan Malaysia (SPM) examination this year.